THE PROTECTION OF CONSUMERS’ RIGHTS AND THE APPLICATION OF CRIMINAL LAW IN THE UNLAWFUL OPERATION OF SERVICES AND CONTENT SERVICE APPLICATIONS - Makarim, Edmon (UI Scholars Hub, 2012)
Media reports on cases of the theft of pre-paid pulses taking place nowadays have created a misunderstanding in terms of the appropriate application of criminal law. In the context of existing legal provisions concerning consumer protection as setf orth both under the Consumer Protection Law as well as in part under the Telecommunications Law, law enforcement agencies are leaning towards applying general criminal provisions (theft) which, after a careful observation of the Indonesian Criminal Code, in fact do not extend to corporate criminal acts. This paper purports to explain that the currently occurring cases of the theft of pre-paid pulses should be adequately dealt with by imposing administrative sanctions by the governing and supervisory agencies, both under the Telecommunications Law as well as the Consumer Protection Law. It is proposed that it would be more effective to apply the Consumer Protection Law in such cases, as it contains provisions concerning the threat of alternative criminal punishment in the form of confinement or fines, along with additional sanctions in the form of an order to pay compensation for damages to consumers accompanied by the seizure and the halting of the application system in use by the Operator and/or CP concerned. It is proposed that in administering a proper telecommunications system to the public, the application of the Consumer Protection Law is likely to be less counter productive as opposed to the application of general criminal provisions, considering that the latter are contradictory to the principles of legal certainty and partnership mandated under the Telecommunications Law itself.